(untitled) (International Journal of Engineering Sciences & Management Research, 2016)
The planned system consists of a wise card capable of storing the fingerprint of the particular person. which is used for authentication of the vehicles. Vehicles like cars and bikes need to have a wise card reader capable of reading the particular license. identical automobile need to have the fingerprint reader device. A person, requires to drive the vehicle, need to insert the cardboard inside the vehicle and swipe his/her finger. If it’s matched with the swiped finger print, he/she can proceed for ignition, otherwise ignition will not work. Moreover, the security harness detector verifies thus promotes the user to wear the security harness before driving and alcohol sensor is to boot interfaced throughout this project therewith if the thrust is drunk or beneath the influence of alcohol the ignition will stop working automatically. this may increase the security and safety of vehicles and so the motive force too preventing accidents.